Better late than never (or early): Music training in late childhood is associated with enhanced decision-making. (September 2018) - Smayda, Kirsten E; Worthy, Darrell A; Chandrasekaran, Bharath
Decision-making is critical to everyday life. Here we ask: to what extent does music training benefit decision-making? Supported by strong associations between music training and enhanced cross-domain skills, we hypothesize that musicians may show decision-making advantages relative to non-musicians. Prior work has also argued for a "critical period" for cross-domain plasticity such that beginning music training early enhances sensorimotor brain regions that mature early in life. Given that brain regions supporting decision-making begin maturing late in childhood, we hypothesized that an advantage in decision-making may only be present in musicians who began music training later in childhood. To test this hypothesis, young adults who began music training before and after 8 years of age (early-trained musicians, ET; late-trained musicians, LT, respectively) and non-musicians (NM) performed a decision-making task. We found a decision-making advantage in LT relative to ET and NM. To better understand the mechanism of the LT advantage, we conducted computational modeling on participant responses and found that LT were less biased by recent outcomes and incorporated longer strings of outcomes when deciding among the choice options. These results tentatively suggest that music training may confer decision-making enhancements, and carry strong implications for the utility of music training in childhood.